Upaya Guru dalam Menumbuhkan Kreativitas Belajar Tematik di Masa Pandemi pada Siswa Kelas II C MIN 1 Bantul Yogyakarta - Kowi Dhukhurmatin; Munjahid; Mujawazah (QuranicEdu: Journal of Islamic Education, 2022)
This research was motivated by the condition of the world being affected by the coronavirus outbreak, so it was important to plan a strategy in growing thematic learning creativity in students through online learning strategies. This research aimed to determine: 1) the teacher's efforts in fostering thematic learning creativity during the pandemic in class II C MIN 1 Bantul students in the 2020/2021 academic year. This research was a qualitative research with descriptive-analytical type. The approach to this research was a case study. Data was collected by means of observation, interviews, and documentation. While the data analysis used the analysis of John W. Cresswell. The research results revealed that: (1) the implementation of online learning systems in fostering thematic learning creativity, namely: (a) utilizing social media applications, (b) synergizing and collaborating with students' parents, (c) emphasizing learning on life skills, (d) emphasize good habits, (e) apply learning evaluation. (2) the implications of online learning systems for the growth of children's creativity, namely: (a) less optimal inculcation of cognitive aspects in students, (b) students were more 'literate' technology, and (c) students became more focused in the learning process.